2018
DOI: 10.1007/s40263-018-0557-x
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative Pharmaco-Electroencephalography in Antiepileptic Drug Research

Abstract: Pharmaco-electroencephalography (pharmaco-EEG) has never gained great popularity in epilepsy research. Nevertheless, the electroencephalogram (EEG) is the most important neurological examination technique in this patient population. Development and investigation of antiepileptic drugs (AEDs) involves EEG for diagnosis and outcome evaluation. In contrast to the common use of the EEG for documenting the effect of AEDs on the presence of interictal epileptiform activities or seizures, quantitative analysis of dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 71 publications
0
26
0
3
Order By: Relevance
“…However, some studies report increased connectivity (5, 7), and other studies report decreased connectivity (6, 73) or complex patterns of increased and decreased connectivity (24). It is likely that these differences are influenced by the type of epilepsy studied (genetic/idiopathic vs. focal/lesional epilepsy), clinical differences (e.g., seizure rate/freedom), the methods such as the choice of the frequency band, processing variants used and, possibly, medication (74). All these factors will need to be better addressed in future studies to allow better comparability.…”
Section: Source Connectomes In Epilepsymentioning
confidence: 99%
“…However, some studies report increased connectivity (5, 7), and other studies report decreased connectivity (6, 73) or complex patterns of increased and decreased connectivity (24). It is likely that these differences are influenced by the type of epilepsy studied (genetic/idiopathic vs. focal/lesional epilepsy), clinical differences (e.g., seizure rate/freedom), the methods such as the choice of the frequency band, processing variants used and, possibly, medication (74). All these factors will need to be better addressed in future studies to allow better comparability.…”
Section: Source Connectomes In Epilepsymentioning
confidence: 99%
“…Therefore, the detection of EEG during and after drug withdrawal is also worthy of attention. In recent years, the value of quantitative pharmaco-EEG in predicting and evaluating treatment response and side effects of ASM has started to gain scientific interest ( 40 ). Studies of patients with temporal lobe epilepsy have shown that quantitative EEG at both resting state and after treatment has a high predictive significance for the effect of drug treatment, which may offer new prognostic biomarkers for patients with epilepsy ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we provide more information about epilepsy onset, duration, seizure type, seizure frequency, and medication in Supplementary Table 2. Höller et al (2018) provides an overview of pharmaco-EEG studies with anti-epileptic drugs (AEDs) based on 37 studies. Different AEDs had different effects on oscillatory activity.…”
Section: The Effect Of Epilepsy On Wave Occurrence Ratesmentioning
confidence: 99%